2014
DOI: 10.1093/mnras/stu2215
|View full text |Cite
|
Sign up to set email alerts
|

Formation of disc galaxies in preheated media: a preventative feedback model

Abstract: We introduce a semi-analytic galaxy formation model implementing a self-consistent treatment for the hot halo gas configuration and the assembly of central disks. Using the model, we explore a preventative feedback model, in which the circum-halo medium is assumed to be preheated up to a certain entropy level by early starbursts or other processes, and compare it with an ejective feedback model, in which baryons are first accreted into dark matter halos and subsequently ejected out by feedback. The model demon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
55
1
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(60 citation statements)
references
References 145 publications
(192 reference statements)
3
55
1
1
Order By: Relevance
“…Others that use additional physical assumptions find important correlations of size with variables beyond halo mass and spin, but neglect the scatter in sizes (e.g. Lu, Mo & Wechsler 2015). The empirical identification of the aspects of the galaxy-halo connection responsible for realistic size distributions -and correlations with velocity -will be of use in constraining such models and guiding the choice of inputs.…”
Section: Introductionmentioning
confidence: 99%
“…Others that use additional physical assumptions find important correlations of size with variables beyond halo mass and spin, but neglect the scatter in sizes (e.g. Lu, Mo & Wechsler 2015). The empirical identification of the aspects of the galaxy-halo connection responsible for realistic size distributions -and correlations with velocity -will be of use in constraining such models and guiding the choice of inputs.…”
Section: Introductionmentioning
confidence: 99%
“…For example, these models predicted isentropic cores particularly in the low mass clusters (Ponman et al 2003) and an excess of entropy in the outskirts of the clusters (Voit et al 2003) which are not consistent with observations. The idea of preheating has endured and has found resurgence in recent times (see Pfrommer et al (2012); Lu et al (2015) and references therein). Pfrommer et al (2012) suggested time dependent entropy injection due to TeV blazars which provide uniform heat at z ∼ 3.5 peaking near z ∼ 1 and subsequent formation of CC (NCC) clusters by early forming groups (late forming groups) while Lu et al (2015) explored preventative scenario of feedback in which the circum-halo medium is heated to finite entropy.…”
Section: Introductionmentioning
confidence: 99%
“…Ikeuchi 1986; Efstathiou 1992; Navarro & Steinmetz 1997; ⋆ E-mail:kana.matsui@nao.ac.jp; babajn@elsi.jp Gnedin 2000;Okamoto et al 2008), and preheating of the intergalactic medium (IGM) by gravitational pancaking (e.g. Mo et al 2005;Lu et al 2015) have been considered, while for high-mass galaxies, active galactic nucleus (AGN) feedback (e.g. Croton et al 2006) and gravitational heating (e.g.…”
Section: Introductionmentioning
confidence: 99%